ANALISIS KUALITAS PELAYANAN RUMAH SAKIT TERHADAP IMAGE (Studi pada Rumah Sakit Pemerintah “X" di Jakarta Selatan) - willy Arafah (Media Riset Bisnis & Manajemen, 2004)
A good corporate image serves as an effective strategy in winning the competition with other businesses of the same type. Leading companies who wish to keep their status should always keep service quality mind. It has to be an absolute concem as the organization does not only have to face the competitors but also the customers who continuously change, vary, and are aware of their needs. Therefore, continuous enhancement of service quality has to be pro- vided. This study is aimed at 1) determining the service quality level of public hospital, form the patient perspective; 2) determining influence of service quality on corporate image. Service quality is measured in six dimensions know as servqual technique. The six dimensions serve as Tangibility (x1), Reliability (x2), Responsiveness (x3), Assurance (x4). Empathy (x5), Accesibitity and Affordability (X6). The research was conducted at the regional publichospital, with sampling was done by convenience random sampling technique obtain respondents. Gap analysis was used by comparing performance and expectation, while regression analy- sis was used by the inter-variable relationship of the hypothesis. In conclusion, the result of this study support some theories developed by the Parasuraman (Servqual), Brown (Cus- tomer Satisfaction/Revenue Enhancement Models) and Elhaitammy (Service Excellence). Furthermore, this confims the hypothesis that significant influence is evident quality on the corporate image.